Hypothetical Learning Trajectory Design On Rotation Topic Using Photography Context - Tri Oktaria; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Ely Susanti; Budi Mulyono (Didaktik Matematika, 2025)
This research aims to design a learning trajectory on rotation topic using photography context for junior high school students. The method used in this study is design research, with 3 stages, namely the preliminary design stage, the design experiment stage and the retrospective analysis stage. This study uses the Indonesian Realistic Mathematics Education (PMRI) learning approach. The Hypothetical Learning Trajectory (HLT) design is made through learning activities using a photography context. The research subjects were grade IX students of SMP Bina Warga Palembang. The results of this research are in the form of HLT design in learning geometric transformation on rotation topic using the context of photography with the learning trajectory being that students take photo objects freely, draw the results of the photos they take with certain rules, record the ends of the photo objects as starting points and determine the results of the rotation, finding the relationship between the two and finding the rotation formulas